Prevalence and factors associated with self-reported diabetes mellitus in Gauteng Province in South Africa - Chiwanda Banda, Jonathan (My University, 2018)
Introduction Diabetes mellitus is a global public health challenge because of its increasing prevalence particularly in low and middle income countries. The prevalence of diabetes varies between countries because of differences in environmental factors and genetic susceptibility. The aim of this study was to estimate the prevalence and determine factors associated with self-reported diabetes mellitus in Gauteng province in South Africa. Methods This was a cross sectional study that used secondary data from a household survey done in 2015 by Gauteng City-Region Observatory. The study had 30,002 participants aged 18 years and above who were selected through multistage sampling technique in which enumeration areas (EAs) as primary sampling unit were drawn using probability proportional to size. Random eligible participants per household were sampled. Prevalence was estimated as a proportion of total diabetes cases from the study sample. Logistic regression was used to analyse the association between diabetes status as an outcome and certain socio-demographic and comorbidity characteristics. Results The estimated prevalence of self-reported diabetes was 11.23% (95% CI: 10.87-11.59) overall, 12.19% (95% CI: 11.69-12.69) in women and 10.13% (95% CI: 9.63-10.63) in men. Factors significantly associated with diabetes were being migrants who had lived in the province for less than ten years [adjusted Odds Ratio (aOR): 0.57, 95% CI: 0.47-0.69], advanced age (aOR: 1.01, 95% CI: 1.01-1.02), socioeconomic status (p<0.0001), Indian race (aOR: 1.52, 95% CI: 1.19-1.94). In addition, a number of comorbidities were associated with diabetes, namely hypertension, heart disease/stroke, HIV/AIDS, tuberculosis, cancer, asthma and mental illness Conclusion The study findings reported higher prevalence of self-reported diabetes mellitus among adult population in Gauteng province compared to national prevalence (8.4%). Migrants who had stayed less than ten years and participants with low socioeconomic status were protected against diabetes. We recommend scaling up public health interventions that would reduce further growth of the disease particularly targeting higher risk population sub-groups. Keywords: Diabetes mellitus, prevalence, Gauteng province.
A research report submitted to the School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Masters of Science in Epidemiology (Epidemiology and Biostatistics). January, 2018.
Keywords: Diabetes Mellitus